Ring-shaped corona proteins influence the toxicity of engineered nanoparticles to yeast. Issue 6 (10th May 2018) - Ruotolo, Roberta; Pira, Graziella; Villani, Marco; Zappettini, Andrea; Marmiroli, Nelson
Abstract : Proteins involved in crucial metabolic pathways form the "hard" corona and affect the bioactivity of metal-based engineered nanoparticles. Abstract : Engineered nanoparticles (ENPs) have found applications in different fields varying from medical science to electronics. The increasing interest in these materials, fuelled by the potential benefits of their use, has not as yet been matched by a concerted effort to gain a full understanding of potential negative effects they may have on the environment and on human health. In a biological environment, ENPs become coated by a so-called "protein corona", the structure of which defines their biological identity. The present research set out to characterize the interaction between cadmium sulphide quantum dots (QDs) and yeast cells, isolating and identifying the set of proteins which were adsorbed on the QD surface using liquid chromatography-mass spectrometry followed by an in silico protein analysis. Ring-shaped proteins were particularly prone to binding, and electrostatic and hydrophobic interactions were central for this interaction. QDs strongly increased the transcript levels of genes encoding the major hard corona proteins indicating a mechanism of genetic compensation in response to the "physical sequestration" of these proteins in the QD corona in vivo . The toxicological implications of the protein corona formation were explored using yeast mutant strains carrying deletions in genes encoding the corona proteins. Interestingly, these mutants were tolerant to doses of QDs that were lethal to wild type cells. These results reveal that the hard protein corona mediates the toxicity of QDs in yeast and a major resolution of this interaction at the molecular level is crucial for a better understanding of the in vivo response of ENPs.